The potential role of the right to procreative autonomy in Irish law in relation to the use of assisted reproductive technologies - Byrne, Laura (Trinity College (Dublin, Ireland). School of Law, 2013)
This thesis promotes the recognition of a right to procreative autonomy in Irish law in relation to the use of assisted reproductive technologies (ARTs). Ireland has yet to legislate for ARTs. The thesis suggests that the right to procreative autonomy under the Irish Constitution should protect the interests of individuals in future legislation. It could also enable the Irish courts to police any regulation of ARTs, or afford weight to individual interests in the absence of legislation in this jurisdiction.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.